Online Professional Development for English Teachers: An Autoethnographic Study - Karki, Sujeet; Neupane, Bharat Prasad (English Language Teaching Perspectives, 2025)
The COVID-19 pandemic had sparked a huge transformation in the educational landscape, driving educators and learners to move from the physical to the virtual classroom. This autoethnographic study examines my professional development activities during and after the pandemic. This study has emphasized the role of technology and social connections as a crucial part of professional growth during the professional journey of an English language teacher. The data were collected from memory work, anecdotes, and experiences from personal and professional journeys. The connectivism theory was used to support the theoretical concerns. The findings demonstrated that various online teacher professional development activities like online conversation clubs, discussion forums, webinars and being part of online international organizations like IELTA, contributed to my professional journey. Based on the findings and conclusion, the research recommends including the voices of educators from diverse contexts and expanding its area impacting the online teacher professional development. This article was written based on the online teacher professional development activities of the first author, who is referred to using the first-person pronoun ’I.’ The second author contributed by providing suggestions to the first author during the writing process, reviewing the contents, editing, and finalizing the article.